Alpha1‐adrenergic stimulation selectively enhances endothelium‐mediated vasodilation in rat cremaster arteries. Issue 9 (13th May 2018) - Mishra, Ramesh C.; Rahman, Mohammad M.; Davis, Michael J.; Wulff, Heike; Hill, Michael A.; Braun, Andrew P.
Abstract: We have systematically investigated how vascular smooth muscle α 1 ‐adrenoceptor activation impacts endothelium‐mediated vasodilation in isolated, myogenically active, rat cremaster muscle 1A arteries. Cannulated cremaster arteries were pressurized intraluminally to 70 mmHg to induce myogenic tone, and exposed to vasoactive agents via bath superfusion at 34°C. Smooth muscle membrane potential was measured via sharp microelectrode recordings in pressurized, myogenic arteries. The α 1 ‐adrenergic agonist phenylephrine (25–100 nmol/L) produced further constriction of myogenic arteries, but did not alter the vasorelaxant responses to acetylcholine (0.3  μ mol/L), SKA‐31 (an activator of endothelial Ca 2+ ‐dependent K + channels) (3  μ mol/L) or sodium nitroprusside (10  μ mol/L). Exposure to 0.25–1  μ mol/L phenylephrine or 1  μ mol/L norepinephrine generated more robust constrictions, and also enhanced the vasodilations evoked by acetylcholine and SKA‐31, but not by sodium nitroprusside. In contrast, the thromboxane receptor agonist U46619 (250 nmol/L) dampened responses to all three vasodilators. Phenylephrine exposure depolarized myogenic arteries, and mimicking this effect with 4‐aminopyridine (1 mmol/L) was sufficient to augment the SKA‐31‐evoked vasodilation. Inhibition of L‐type Ca 2+ channels by 1  μ mol/L nifedipine decreased myogenic tone, phenylephrine‐induced constriction and prevented α 1 ‐adrenergic enhancement of endothelium‐evoked vasodilation; these latter deficits were overcome by exposure to 3 and 10  μ mol/L phenylephrine. Mechanistically, augmentation of ACh‐evoked dilation by phenylephrine was dampened by eNOS inhibition and abolished by blockade of endothelial KCa channels. Collectively, these data suggest that increasing α 1 ‐adrenoceptor activation beyond a threshold level augments endothelium‐evoked vasodilation, likely by triggering transcellular signaling between smooth muscle and the endothelium. Physiologically, this negative feedback process may serve as a "brake" to limit the extent of vasoconstriction in the skeletal microcirculation evoked by the elevated sympathetic tone. Abstract : We have systematically investigated how vascular smooth muscle α1‐adrenoceptoractivation impacts endothelium‐mediated vasodilation in isolated, myogenically active, rat cremaster muscle arteries. Collectively, our data suggest that increasing α1‐adrenoceptor activation beyond a threshold level augments endothelium‐evoked relaxation by Ca2+‐dependent vasodilators, likely by triggering transcellular signaling with the endothelium. Physiologically, this negative feedback process may serve as a "brake" to limit the extent of vasoconstriction in the skeletal microcirculation evoked by the elevated sympathetic tone.